81.4k views
3 votes
Solve the equation.
x-2/5=2/3-3x-2/6

2 Answers

7 votes

Answer:

11/48

Explanation:

x-2/5=2/3-3x-2/6

collect like terms

x-2/5 + 3x = 2/3 - 2/6

taking LCM on both sides

[(x-2) + 5(3x)]/5 = [2(2) -2]/6

(16x - 2)/5 = 2/6

cross multiply

6(16x - 2) = 5(2)

96x - 12 = 10

96x = 22

therefore; X = 22/96

= 11/48

CHECK:

(11/48 - 2)/5 = 2/3 - 3(11/48) - 2/6

(-85/48)/5 = 2/3 - 11/16 - 2/6

-85/48 × ⅕ = -17/48

-17/48 = -17/48

User Xaviera
by
5.2k points
5 votes

Answer:


x=(11)/(60)

Explanation:

Given the equation


x-(2)/(5)=(2)/(3)-3x-(2)/(6)

Lets solve for x.

Simplify the right side of the equation.

Cancel the common factor of 2 and 6 .

Factor 2 out of 2 .


x-(2)/(5)=(2)/(3)-3x-(2(1))/(2(3))


x-(2)/(5)=(2)/(3)-3x-(1)/(3)

Combine the numerators over the common denominator.


x-(2)/(5)=-3x-(2-1)/(3)


x-(2)/(5)=-3x-(1)/(3)

Move all terms containing x to the left side of the equation.

Add
3x to both sides of the equation.


x-(2)/(5)+3x=(1)/(3)

Add
x and
3x.


4x-(2)/(5)=(1)/(3)

Move all terms not containing x to the right side of the equation.

Add
(2)/(5) to both sides of the equation.


4x=(1)/(3)+(2)/(5)

To write
(1)/(3) as a fraction with a common denominator, multiply by
(5)/(5) .


4x=(1)/(3)*(5)/(5) +(2)/(5)

To write
(2)/(5) as a fraction with a common denominator, multiply by
(3)/(3)


4x=(1)/(3)*(5)/(5) +(2)/(5)*(3)/(3)

Simplify.

Write each expression with a common denominator of 15 , by multiplying each by an appropriate factor of 1 .


4x=(11)/(15)

Divide each term in
4x=(11)/(15) by 4 and simplify.


x=(11)/(60)

User Nikola Jovic
by
4.6k points